Efektifitas Tabayyun Di Media Online Bagi Generasi Milenial - Eny Latifah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
The aim of the research is to make the millennial generation aware of the importance of Tabayyun in reviewing hoax information both in the real world and in cyberspace which is often spread on online media such as Facebook, Instagram, and others. With this study, it is hoped that the millennial generation can realize peace in this world; especially in Indonesia. This research method uses a qualitative approach using developmental studies with the Hypodermic Needle Theory theory or the syringe theory. Data collection was carried out by observation, interviews, documentation, data analysis and data validity including validity testing, lengthening observations, research persistence and triangulation. Then the authors drew conclusions from the results of relevant information. The results showed Tabayyun or re-assessment in examining information from social media; for the millennial generation, it is very important as a hoax and contains slander that is still circulating in cyberspace and that has spread in the real world. Tabayyun also has an important role in maintaining the peace of the ummah so as not to be swallowed up by hoaxes and can live peacefully in the community.